Criminal Liability Of Perpetrators Who Promote Online Gambling Based On (A Study Of Decision Number 91/Pid.Sus/2024/Pn Lsm) - I Gede Darma Yuda Suarpana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
The development of information technology has driven the shift of crimes into cyberspace, including the increasingly widespread practice of online gambling. Promotion through social media by influencers has expanded pub-lic access to gambling activities and generated serious social and legal im-pacts. This study examines the regulation and criminal liability of perpetra-tors promoting online gambling in Indonesia through the analysis of the Lhokseumawe District Court Decision Number 91/Pid.Sus/2024/PN Lsm. The method employed is normative juridical research with statutory, concep-tual, and case study approaches. The results of the study indicate that the regulation of online gambling promotion is governed under Articles 303 and 303 bis of the Indonesian Criminal Code, Law Number 7 of 1974 concerning Gambling Control, and Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of the Electronic Information and Transactions Law as amended by Law Number 1 of 2024. Criminal liability is based on the ele-ments of conduct and fault (mens rea), whereby perpetrators may be regard-ed as participants or instigators. The court decision affirms that gambling-related content accessible to the public through social media fulfills the ele-ments of a criminal offense and may be subject to sanctions in accordance with applicable legal provisions.